(untitled) (Journal of Engineering Science, 2023)
The concentrations of four heavy metals in rice grains and the health risk assessments of the metals were studied. Sixteen rice samples were gathered from Rajshahi, Bangladesh. Average lead, chromium, manganese, and cadmium concentrations measured in rice samples were 6.87, 0.43, 44.58, and 1.13 mg/kg, respectively. The concentration level found in most rice samples is greater than the acceptable limit as set by WHO. The risk assessment was done by using the intended hazard ratio and target carcinogenic risk where the values for the lead, manganese, and cadmium quotient were greater than 1. The target cancer-causing risk values for a maximum number of samples are lower than 10-4, which is considered safe. However, target carcinogenic risk values for cadmium are higher than 10-4, which is considered a carcinogenic risk. The results of the current investigations suggest that appropriate measures should be taken to determine the cause and origin of this heavy metal contamination. Journal of Engineering Science 14(1), 2023, 29-41